GAMG alleviates liver fibrosis through inducing ferroptosis in inflammatory macrophages via the IRF1/SLC7A11 signaling pathway - Qing Pang; Shuai Zhou; Yong Wang; Hongtao Pan; Zhicheng Wang; Xiliang Qin; Chao Zhu; Shilei Chen; Huichun Liu; Xiaosi Hu; Hao Jin (Redox Biology)
The activation of inflammatory macrophages plays a pivotal role in the development of liver fibrosis (LF). Ferroptosis contributes to the clearance of inflammatory macrophages and the release of profibrotic factors. Glycyrrhetic Acid 3-O-Mono-β-d-glucuronide (GAMG) is a natural compound, the potential role of which on LF remains uncertain. In this study, GAMG treatment significantly reduced hepatocyte steatosis, fibroplasia, inflammatory cell infiltration, and collagen fiber deposition in LF mice. In addition, GAMG remarkably decreased the content of collagen protein and improved liver function indicators. Single-cell RNA sequencing revealed that GAMG significantly affected the changes of macrophage subsets in LF, and Funrich analysis identified IRF1 as a key transcription factor regulating the macrophage genome. IRF1 was significantly increased while ferroptosis related SLC7A11 was significantly down-regulated in GAMG treated inflammatory macrophages. Mass spectrometry metabolomics analysis showed that GAMG significantly affected metabolites associated with LF. In vivo and in vitro experiments further verified that GAMG induced ferroptosis of inflammatory macrophages through the IRF1/SLC7A11 axis, and ultimately alleviated LF. Therefore, GAMG induces ferroptosis of inflammatory macrophages by activating the IRF1/SLC7A11 axis, which provides a new strategy for the treatment of LF.